Proceso de atención de enfermería en paciente con quemaduras de tercer grado - Rodríguez Alcívar, Nidia Beatriz (2018)
The process of nursing care lies in making a comprehensive assessment of the patient, from a holistic perspective, determining the degree of burn suffered, the influence and depth of the injury. The present case shows the results of the evaluation of the nursing care process in a patient with third degree burns. For this purpose, a clinical assessment and the respective laboratory tests were carried out. My general objective was to apply the process of nursing care in patients with third-degree burn, for which a cephalo-caudal examination was performed followed by assessment by Marjorie Gordon functional patterns by means of which dysfunctional patterns were detected with which proceeded to perform the respective nursing diagnoses to establish a care plan and intervene according to the needs of the patient. A follow-up was carried out in which the nursing interventions were the main factor for the improvement of the patient along with the pharmacological treatment that was administered. It is determined that the process of nursing care is an elementary tool to potentiate the nursing care and care process, this allows a better diagnosis of the complications that arise in health, as well as providing a safe response and visualization of the clinical improvement of patients.